Detection of SARS-CoV-2 RNA in the corneal epithelium of a patient after recovery from COVID-19 - Irene C. Kuo; Heba H. Mostafa (American Journal of Ophthalmology Case Reports, 2021)
Purpose: To report a case of a patient presenting with unilateral keratouveitis associated with ocular hypertension six weeks after being discharged from the hospital for COVID-19. Ocular specimens were obtained for testing. Observations: A 69-year-old African American woman developed poor vision while hospitalized for COVID-19 in April but did not seek ophthalmic care until end of May. She had an edematous cornea, stromal keratitis, and highly elevated intraocular pressure by June. After lack of response to oral valacyclovir, aqueous fluid and swabs of her conjunctiva and limbal epithelium with corneal epithelium anterior to the limbus were sent for real-time polymerase chain reaction (PCR) for herpes simplex virus, herpes zoster virus, and severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Epithelium from the cornea and limbus was positive for SARS-CoV-2 by PCR; specimens from the other two ocular sites were negative. All specimens were negative for herpes simplex virus and varicella zoster virus. The patient refused further treatment despite intraocular pressure above 50 mm Hg at last follow-up. Conclusions and Importance: Although SARS-CoV-2 and severe acute respiratory syndrome coronavirus (SARS-CoV) have been detected by PCR in the conjunctiva and tears of patients with acute respiratory infection, presence in corneal tissue has not been described. In addition, no one has studied whether ocular tissues in convalesced patients can harbor viral RNA. Here we describe unilateral keratouveitis in a convalesced patient whose corneal epithelium/limbal tissue was positive for SARS-CoV-2 by PCR. Further investigation is required to determine whether active viral replication or viral remnants account for this result.